Respuesta :

[tex]\bf y+2=\cfrac{1}{3}(x-6)\implies y+2=\cfrac{1}{3}x-2 \\\\\\ y=\cfrac{1}{3}x-4\qquad \impliedby \begin{array}{|c|ll} \cline{1-1} slope-intercept~form\\ \cline{1-1} \\ y=\underset{y-intercept}{\stackrel{slope\qquad }{\stackrel{\downarrow }{m}x+\underset{\uparrow }{b}}} \\\\ \cline{1-1} \end{array}[/tex]

Answer:

[tex]y = \frac{1}{3} x - 4[/tex]

Step-by-step explanation:

Given equation :-

[tex]y + 2 = \frac{1}{3} (x - 6)[/tex]

• Slope intercept form is

y = mx + c

where , m is slope of the straight line

and c is y intercept of the line !

Solving and simplifying the given equation ,

[tex]3y + 6 = x - 6 \\ \\ 3y = x - 6 - 6 \\ \\ 3y = x - 12[/tex]

[tex]y = \frac{1}{3} x - \frac{12}{3 } \\ \\ y = \frac{1}{3} x - 4[/tex]

So, m = 1/3 and c = ( -4 )

hence , the required slope intercept form of the equation is

[tex]y = \frac{1}{3} x - 4[/tex]